Enriching product exposure in e-commerce through a hedonistic and utilitarian cue - Andrzej Szymkowiak; Urszula Garczarek-Bąk; Armand Faganel (Wine Economics and Policy, 2024)
With the projected growth in the global wine market, the ongoing impact of the COVID-19 pandemic, and the increasing prevalence of e-commerce, a pressing need arises to devise unique and engaging ways to present product offerings. While prior research has shed light on the potential of online sales platforms for wineries and the role of wine bottle labels in influencing consumer purchasing behavior, scant attention has been given to the presentation of wine products in the realm of e-commerce. Therefore, the primary objective of this study is to examine the impact of including visual cues (symbols) in online product displays on individuals’ perceptions of the product and their likelihood to make a purchase. Specifically, we aim to investigate how the placement of elements related to wine consumption, such as a ‘Glass’, and the representation of the product’s raw materials, such as a bunch of ‘Grapes’, affect consumer purchasing choices. The results from a simulated online wine store demonstrate the substantial influence of including a ‘Glass’ symbol on consumers’ selections. Furthermore, a series of eye-tracking laboratory experiments conducted in Poland, involving a total of 140 participants, provides deeper insight into underlying mechanisms. These findings reveal that augmenting a wine product with a hedonic symbol, such as a ‘Glass’, significantly enhances consumer perception of the product. Additionally, it exerts influence on their ‘Product Attitude’ and ‘Product Taste’ assessment, both of which are integral components of product perception. This study has the potential to offer valuable insights for wine marketers, e-commerce retailers and researchers specializing in the field of consumer behavior and marketing. Beyond the wine industry, the implications of this research extend to other sectors that rely on e-commerce platforms for sales.